(untitled) (Revista de Ciências Agroveterinárias, 2012)
The objective of this study was to evaluate the behavior of the cadmium (Cd), lead (Pb), nickel (Ni), mercury (Hg) and Chromium (Cr) in soil after application of a mixture of lime mud, dregs and grits (LMD+G) resultant from a cellulose industry process, an experiment with five years time was implemented on a typical Distrofic Red Latosol according to the Brazilian system of soil classification. Corn was cultivated five years in the experimental area. The treatments were composed of fractions of mixture based on the recommendation to rise pH at 6,0, by SMP indicator; dolomitic and calcitic lime and mixture of dolomitic lime and LMDG were used like a control. Treatments were arranged in a randomized complete blocks split-plots design with three replications. One year after first application, the treatments were reapplied as a split factor. In quantities tested, the use of the LCDG does not change the total levels of Cd, Pb, Hg, Ni, and Cr in soil and decreases the levels of Pb soluble decreasing him availability.